1984
DOI: 10.1017/s0033583500005308
|View full text |Cite
|
Sign up to set email alerts
|

Electron spin polarization of photosynthetic reactants

Abstract: Photosynthesis is the conversion of the quantum energy of light into the chemical energy of complex organic molecules and organized cellular structures in plants and in some bacteria. The processes of photosynthesis span the time domain of subpicoseconds to the millennia of slow-growing trees, its study brings together such diverse disciplines as photophysics, biochemistry, botany and ecology. In the last few decades tremendous progress has been made in understanding the multivarious chemical reactions that ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 199 publications
(273 reference statements)
2
38
0
Order By: Relevance
“…Since the time the first reaction center was isolated from the purple bacterium Rhodobacter sphaeroides [122] (formerly Rhodopseudomonas sphaeroides [65]), an enormous literature has grown on the properties of bacterial reaction centers (see general reviews [56,106,112,114]). This review will focus on the primary charge separation process in reaction centers isolated from the purple photosynthetic bacteria.…”
Section: Scope Of This Reviewmentioning
confidence: 99%
“…Since the time the first reaction center was isolated from the purple bacterium Rhodobacter sphaeroides [122] (formerly Rhodopseudomonas sphaeroides [65]), an enormous literature has grown on the properties of bacterial reaction centers (see general reviews [56,106,112,114]). This review will focus on the primary charge separation process in reaction centers isolated from the purple photosynthetic bacteria.…”
Section: Scope Of This Reviewmentioning
confidence: 99%
“…The radical pair is born in a pure electronic singlet state S 0 , which evolves coherently into a triplet state T 0 , while the other two triplet states (T ?1 and T -1 ) are not populated at high magnetic fields. This high electron polarization delocalized in the S 0 -T 0 manifold is detected as photochemically induced dynamic electron polarization [17,18]. In this context, electron polarization of the radical pair corresponds to selective population of the two noneigenstates having the magnetic quantum number m = 0 and being in the S 0 -T 0 manifold.…”
Section: Introductionmentioning
confidence: 99%
“…Low temperature polarized signals of PS I of orientated and unorientated material were observed by a number of authors (reviewed in Hoff, 1984). The ESP spectrum of unorientated PSI particles, which is very much like the low temperature ESP signal of bacteria, was simulated by Gast (1982;Gast et al, 1983) following the suggestions of Pedersen (1979) on ESP in a multiple acceptor system.…”
Section: The Plant Photosystemsmentioning
confidence: 99%
“…As has been pointed out above, this is probably not a good approximation for the distances of the radicals encountered in the RC. Previous attempts to include in lineshape simulations of polarized signals an axial dipolar interaction were not satisfactory (McCracken, 1983;McCracken and Sauer, 1983;Hoff, 1984) but recently Hore et al (1986) presented a transparent treatment of this problem. They showed that for random samples and the type of radicals found in the RC (D', A;, A;) D plays only a role in the transfer of polarization from A; to A;, because only A, has a significantly anisotropic g-term.…”
Section: Bacterial Reaction Centersmentioning
confidence: 99%
See 1 more Smart Citation